Introduction of a New Standardized Assessment Score of Spine Morphology in Osteogenesis Imperfecta - Koerber, F.; Schulze Uphoff, U.; Koerber, S.; Schönau, E.; Maintz, D.; Semler, O. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: Osteogenesis imperfecta (OI) is a rare hereditary disease leading to multiple bone deformities and fractures. In the absence of causal therapy, a symptomatic approach is based on treatment with bisphosphonates and physiotherapy. The clinical and radiological manifestations vary. Therefore, standardization and quantification for an objective comparison, especially during therapy, are required. In this paper, radiological changes of the spine are quantified according to their clinical relevance to define a scoring system that transfers the morphological changes into a single value representing the severity of the disease. Materials and Methods: 268 lateral spine X-rays of 95 patients with OI (median age 5.6 years) were assessed. The findings were classified based on their clinical relevance. Results: The three criteria, vertebral compression, thoracolumbar kyphosis and deformity type, were quantified in a new grading system. Based on this, a “severity classification” (1 to 5) was defined with implications for diagnostics and treatment. A mathematical formula that takes into account the three criteria and their correlations to clinical relevance, resulting in a “severity score”, was developed. Conclusion: “Severity classification” and “severity score” introduce a new concept for a standardized evaluation of spine X-rays in patients with OI. For both scientific and routine purposes, it provides the user with a simple and easy-to-handle tool for assessing and comparing different stages of severity prior to and during therapy with detailed accuracy.
Keywords: radiography; spine; osteogenesis imperfecta; score; quantification